Reassessing EOQ-Based Brown Clay Inventory Control for NPK Fertilizer Production: Model Validation and Scenario Analysis - Rizky Pratama; Agung Widarman; Haris Sandi Yudha (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2026)
This study reassesses brown clay inventory control for NPK fertilizer production at PT Pupuk Kujang by replacing a purely formula-driven EOQ application with a retrospective quantitative case-study design that integrates descriptive inventory analytics, arithmetic and semantic data auditing, EOQ identity validation, and scenario-based replenishment analysis. The dataset contains twelve monthly observations for 2023 covering procurement volume, replenishment frequency, and reported cost components. Recalculation from monthly entries yields 13,714.42 tons of annual procurement distributed across 594 reported order events. Monthly procurement is highly variable (coefficient of variation = 0.699), while order frequency is similarly dispersed (coefficient of variation = 0.682). January, February, and November alone account for 49.44% of annual procurement. The audit identifies a critical cost-classification problem: the reported